Characteristics and causes of Deep Western Boundary Current transport variability at 34.5° S during 2009-2014 - Meinen, Christopher S.; Garzoli, Silvia L.; Perez, Renellys C.; Campos, Edmo; Piola, Alberto Ricardo; Chidichimo, María Paz; Dong, Shenfu; Sato, Olga T. (Ocean Science)
The Deep Western Boundary Current (DWBC) at 34.5° S in the South Atlantic carries a significant fraction of the cold deep limb of the Meridional Overturning Circulation (MOC), and therefore its variability affects the meridional heat transport and consequently the regional and global climate. Nearly 6 years of observations from a line of pressure-equipped inverted echo sounders (PIESs) have yielded an unprecedented data set for studying the characteristics of the time-varying DWBC volume transport at 34.5° S. Furthermore, the horizontal resolution of the observing array was greatly improved in December 2012 with the addition of two current-and-pressure-equipped inverted echo sounders (CPIESs) at the midpoints of the two westernmost pairs of PIES moorings. Regular hydrographic sections along the PIES/CPIES line confirm the presence of recently ventilated North Atlantic Deep Water carried by the DWBC. The time-mean absolute geostrophic transport integrated within the DWBC layer, defined between 800-4800 dbar and within longitude bounds of 51.5 to 44.5° W, is -15 Sv (1 Sv Combining double low line 106 m3 s-1; negative indicates southward flow). The observed peak-to-peak range in volume transport using these integration limits is from -89 to +50 Sv, and the temporal standard deviation is 23 Sv. Testing different vertical integration limits based on time-mean water-mass property levels yields small changes to these values, but no significant alteration to the character of the transport time series. The time-mean southward DWBC flow at this latitude is confined west of 49.5° W, with recirculations dominating the flow further offshore. As with other latitudes where the DWBC has been observed for multiple years, the time variability greatly exceeds the time mean, suggesting the presence of strong coherent vortices and/or Rossby Wave-like signals propagating to the boundary from the interior. Fil: Meinen, Christopher S. Atlantic Oceanographic and Meteorological Laboratory; Estados Unidos Fil: Garzoli, Silvia L. ...